(untitled) (Práxis Educativa, 2021)
This article, of a theoretical nature, seeks to problematize conceptual approaches to breaking with the epistemic silencing in the teaching space regarding Afro-Brazilian culture and history in the school space, from the political-legal confrontation. The process of social inferiorization of the black population is discussed under the conceptual of racism proposed by Almeida (2018), by placing it in structural conditions of society. As an epistemological alternative, we bring Paulo Freire’s cultural synthesis (2005) relating decolonial thinking to anti-racist teaching. These theoretical constructs are capable of presenting alternatives to face the dynamics of racism and its forms of manifestation in the school space. In reaction to the breakdown of phenomena that built the situations and conditions of structural racism in Brazil, legal provisions such as Laws 10.639 / 03 and 11.645 / 08 seek to curb racism institutionally reproduced at school. Keywords: Structural racism., Decolonial thought. Anti-racist teaching.